SARMATISM – AN UNFINISHED PROJECT? - Nakoneczny, Tomasz (Porównania, 2018)
The article addresses the problem of the applicability of sarmatism, its ideology, sensitivity, lifestyle, etc., to the contemporary Polish identity discourse. The reference for the considerations is mainly the works of Jan Sowa and Ewa Thompson. The main idea of the article is that the treatment of sarmatism either as an autonomous project (Thompson) or as a recoverable identity (neosarmatism) is impossible and pointless. Any (re)interpretation of sarmatism should take into account the specific purposefulness that can be realized in a specific field (artistic culture, academic discourse, etc.).